2016
DOI: 10.1002/hep.28881
|View full text |Cite
|
Sign up to set email alerts
|

Survival and cost‐effectiveness of sorafenib therapy in advanced hepatocellular carcinoma: An analysis of the SEER–Medicare database

Abstract: Sorafenib is the only chemotherapeutic approved for treatment of advanced hepatocellular carcinoma (HCC). However, its effectiveness in patients with Child‐Pugh class B cirrhosis and any moderating effects of health system characteristics are unclear. We examined the survival and cost‐effectiveness associated with sorafenib in elderly patients with advanced HCC. We performed an analysis of Medicare beneficiaries with HCC diagnoses from 2007 to 2009. We compared advanced stage patients with HCC (American Joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 35 publications
2
79
0
Order By: Relevance
“…Second, most patients present with various adverse events of sorafenib, with drug-related grade 3 or 4 adverse events, according to the National Institute of Health’s Common Terminology Criteria for Adverse Events version 3.0, observed in 37.4% of Japanese patients participating in the GIDEON study [4]. Finally, as sorafenib treatment is expensive, its associated cost represents a limitation [5]. Although several studies have investigated predictive biomarkers of sorafenib efficacy, there have been no established predictive biomarkers [6-9].…”
Section: Introductionmentioning
confidence: 99%
“…Second, most patients present with various adverse events of sorafenib, with drug-related grade 3 or 4 adverse events, according to the National Institute of Health’s Common Terminology Criteria for Adverse Events version 3.0, observed in 37.4% of Japanese patients participating in the GIDEON study [4]. Finally, as sorafenib treatment is expensive, its associated cost represents a limitation [5]. Although several studies have investigated predictive biomarkers of sorafenib efficacy, there have been no established predictive biomarkers [6-9].…”
Section: Introductionmentioning
confidence: 99%
“…Drugs designed against a specific target of certain cancers will affect the cancer nidus and kill cancer cells without harming neighboring non-cancerous cells [79]. For instance, sorafenib is a molecular-targeted agent for the treatment of HCC with Child-Pugh A liver function [1012]. It is a multi-kinase inhibitor of tumor growth and angiogenesis, which can significantly inhibit C and B-Raf serine/ threonine kinases, vascular endothelial growth factor receptor, platelet-derived growth factor receptor, tyrosine kinases and FLT-3 (fms related tyrosine kinase 3) [1214].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, sorafenib is a molecular-targeted agent for the treatment of HCC with Child-Pugh A liver function [1012]. It is a multi-kinase inhibitor of tumor growth and angiogenesis, which can significantly inhibit C and B-Raf serine/ threonine kinases, vascular endothelial growth factor receptor, platelet-derived growth factor receptor, tyrosine kinases and FLT-3 (fms related tyrosine kinase 3) [1214]. At present, very few molecular-targeted agents have been approved for the treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…A study published in 2017 analysing the SEER-Medicare database, reported that elderly patients with advanced stage HCC may survive longer if treated with Sorafenib vs placebo (150.5 d vs 62 d, respectively), while the most remarkable factor associated with increased mortality was treatment taking place in an urban setting, although this survival effect was found to be neither prolonged, nor cost-effective in decompensated patients[31]. Currently, a randomized controlled phase 3 study - the B Child Patient-Optimization of Sorafenib Treatment (BOOST) study - is ongoing so as to evaluate the safety and efficacy of Sorafenib in CP B patients and is going to provide helpful information regarding the treatment of patients with decompensated disease[32].…”
Section: Monotherapymentioning
confidence: 99%